2022
DOI: 10.3390/ijerph19042015
|View full text |Cite
|
Sign up to set email alerts
|

Performance Alteration Induced by Weight Cutting in Mixed Martial Arts—A Biomechanical Pilot Investigation

Abstract: Currently, there are pros and cons of research results related to weight cutting in combat sports, resulting in inconclusive results regarding the effects of weight-cut on athletes’ performance, and biomechanical investigations are hardly seen. Therefore, this pilot study tried to fill the gap by initiating an exploration in real-life competitions. It is our hope to add biomechanical insights (advantages/disadvantages) that would discern the impact of weight cutting on competitive performance and help to struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…The analysis of correlation dependencies is widely used in sports science [4,8]. A comparison of the number and strength of connections allows us to evaluate the dynamics of the functional system, which is formed in the process of sports training.…”
Section: Pedagogymentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of correlation dependencies is widely used in sports science [4,8]. A comparison of the number and strength of connections allows us to evaluate the dynamics of the functional system, which is formed in the process of sports training.…”
Section: Pedagogymentioning
confidence: 99%
“…It has been confirmed that the reaction time, strength and accuracy of the strike are among the most important factors in the state of martial arts athletes [2,3,4]. It is proposed to use them for monitoring the functional state of athletes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Same-day weight loss by sweating and fluid deprivation was performed in three studies [ 22 , 23 , 24 ]. The rest of the included studies provide at least a few days for weight loss, also through calorie, energy and/or fluid restriction, specifically a period of 5 days [ 25 , 26 , 27 ], 1 complete week/10 days [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ], or 3/4 weeks [ 35 , 36 ]. In addition, there was a final study comparing progressive RWL performed weeks in advance (3 weeks of calorie restriction) with those performed faster or at shorter notice (59 h prior to weighting) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the RWL typologies and their programming over time, tests applied to aerobic and anaerobic capacity such as the Wingate [ 23 , 25 , 35 , 37 ] or an arm ergometer [ 27 ] stood out as performance analysis methods. Similarly, studies applied specific tests for each combat speciality [ 24 , 25 , 26 , 31 , 33 , 34 , 36 ] and measures aimed at determining the athlete’s strength/performance [ 22 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 ] or psychological state [ 29 , 30 , 32 , 36 ]. In addition to the tests applied to performance, data collection aimed at controlling body composition and weight [ 22 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 34 , 35 , 36 ], and the analysis of blood components [ 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 37 ] and urine [ 22 , 23 , 30 ,…”
Section: Resultsmentioning
confidence: 99%